Kapasitas Kelembagaan Pengelola Desa Wisata Brajan Kabupaten Sleman - Clara Shinta Paskasari (Sekolah Vokasi, Universitas Gadjah Mada, 2020)
Tourism is a rapidly growing sector in Indonesia in recent years. Tourism development is now also moving to villages by raising local wisdom in each place. Brajan is one of the Tourism Villages in Sleman Regency which is included in the growing category. This village is interesting to share because it has great potential and offers a more varied compared to supported villages. One indicator in determining village classification is in terms of capacity of its managers. For this reason, a study was conducted to see the capacity of managers in Brajan to take part in the strategies taken to improve it.The study was conducted qualitatively with data collection methods in the form of interviews, observation, and documentation. Informants in the interview were managers of tourist villages, youth, and the community. The aim is to mapping institutional capacity. Organizational capacity will be seen from managerial aspects, resource management, and participation.The results of this study indicate that managerial does not have the ability to manage programs and processes, but in terms of relationship management and collaboration is good. In terms of managing resources, both human resources and infrastructure, financial and technological resources are still lacking. Participation is still lacking because many managers are already inactive.